2021
DOI: 10.1111/aphw.12309
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness and well‐being in simulated nature

Abstract: People relate to nature physically, cognitively and emotionally, and this relationship fosters their well-being. There are various types of environment according to their degree of human intervention, raising the question of whether they each exert different effects on people, connectedness and well-being. In order to study the extent to which environmental connectedness and well-being are a function of viewing different types of nature, we conducted a study with 454 participants from five different countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
(74 reference statements)
3
12
0
1
Order By: Relevance
“…Thus far, empirical studies of connectedness to nature have mainly centered on closeness with actual forests [e.g., ( 93 )] and urban greenspaces [e.g., ( 94 )]. The present study echoes findings of previous studies, that virtual or simulated nature ( 95 , 96 ) can be one source of human connectedness to nature, as we found that people who intended to expose themselves to virtual nature had a higher connectedness with nature. Although the effectiveness of virtual nature in increasing positive moods is inferior to outdoor exposure ( 97 ), it remains a possible substitute for nature among young adults, especially when actual access to nature is deprived, as was the case during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Thus far, empirical studies of connectedness to nature have mainly centered on closeness with actual forests [e.g., ( 93 )] and urban greenspaces [e.g., ( 94 )]. The present study echoes findings of previous studies, that virtual or simulated nature ( 95 , 96 ) can be one source of human connectedness to nature, as we found that people who intended to expose themselves to virtual nature had a higher connectedness with nature. Although the effectiveness of virtual nature in increasing positive moods is inferior to outdoor exposure ( 97 ), it remains a possible substitute for nature among young adults, especially when actual access to nature is deprived, as was the case during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Mayer et al, 2009). This is in line with a recent study using images as well (Pasca et al, 2021). However, we found no environment-related effects on working memory and mood, which contrasts with studies supporting ART and SRT (cf.…”
Section: Discussionsupporting
confidence: 91%
“…Total sample sizes for all studies ranged from 17 (Jiang et al, 2021) to 306 (Pasca et al, 2021), generally evenly split between nature and urban groups. The total number of participants across all studies was 3201.…”
Section: Experimental Methodsmentioning
confidence: 99%